Theoretical design and investigation of 1, 8-naphthalimide-based two-photon fluorescent probes for detecting cytochrome P450 1A with separated fluorescence signal. Issue 19 (2nd May 2018) - Zhang, Chun; Ren, Ai-Min; Guo, Jing-Fu; Wang, Dan; Yu, Li-Ying
Abstract : Two-photon fluorescent probe for detecting CYP1A enzyme with separated fluorescence signal. Abstract : As a type of enzyme with a terminal oxygen, the CYP1A subfamily possesses the ability to catalyze the reactions of many environmental toxins, endogenous substrates and clinical drugs. The development of efficient methods for the rapid and real-time detection of CYP1A enzyme activity in complex biological systems is of considerable significance for identifying potential abnormalities in these cancer-related enzymes. With this goal, we firstly provided a series of 1, 8-naphthalimide-based two-photon fluorescent chromophores with large two-photon absorption (TPA) cross-sections (500–7000 GM) and remarkable changes in fluorescence spectra upon recognizing the CYP1A enzyme from its theoretical aspect. Moreover, we have thoroughly studied the effects of cyclic acceptor (dichlorobenzene and benzothiadiazole) and donor (fluorene and carbazole) groups on the one-photon absorption (OPA), TPA, and fluorescence properties of CYP1A enzyme probes and the corresponding reaction products. The connection of a heterocycle as the donor group to a 1, 8-naphthalimide-based molecule to form a D–π–A–π–D-type electronic structure can effectively cause red shifts in the absorption and emission wavelengths to facilitate bioimaging in the near infrared (NIR) region, which is attributed to the lower transition energy, larger transition dipole moment and amount of transferred charge. Docking analysis suggests that the two-photon fluorescent probes NCMN-3 and NCMN-5 that were designed will guarantee and achieve excellent selectivity for the CYP1A enzyme.